Emerging Perovskite Nanocrystals-Enhanced Solid-State Lighting and Liquid-Crystal Displays - Ziqian He; Caicai Zhang; Yajie Dong; Shin-Tson Wu (Crystals, 2019)
Recent advances in perovskite nanocrystals-enhanced solid-state lighting (SSL) and liquid-crystal displays (LCDs) are reviewed. We first discuss the development, optical properties, and stability issue of materials, and then we evaluate the performance of SSL and LCDs with perovskite downconverters adopted. In SSL performance evaluation, we investigate the fitting-curve effect in calculations and optimizations where simple Gaussian fitting and precise fitting are compared in detail, and we further optimize for highly efficient, good color-rendering, and human-healthy SSL sources. For LCD performance evaluation, we study the intrinsic tradeoffs between total light efficiency and color gamut coverage. Through optimizations using real line shapes, Rec. 2020 standard coverage as large as 92.8% can be achieved through hybrid integration. Finally, we briefly discuss two future challenges: materials development and device integration. We believe the emerging perovskite nanocrystals are highly promising for next-generation SSL and LCDs.